Irradiation-induced Maillard reaction with glucosamine: an advance method to modify chitosan - Le , Anh Quoc; Dang , Van Phu; Nguyen , Ngoc Duy; Nguyen , Quoc Hien; Ngo , Dai Nghiep (Nuclear Science and Technology, 2026)
: In this study, Maillard reaction with glucosamine (GA) induced by gamma irradiation was applied for improving the stability and antibacterial activity under alkaline condition of chitosan (CTS) and oligochitosan (OC). The mixture solutions of CT and/or OC with GA were irradiated at 25 kGy to form the Maillard reaction products (MRPs), respectively. The formations of MRPs were determined by UV-vis spectrophotometric analyses at the wavelength of 284 nm and 420 nm. The stability improvement of the MRP solutions in alkaline condition was evaluated via the increase of pH value at the precipitation point. The antibacterial activity of the solutions against Escherichia coli was also investigated. The results showed that the CTS-GA MRPs and OC-GA MRPs solutions could remain their stability at pH 7, and the pH values at the precipitation point were found about 7.4 and 11.5, respectively. Moreover, at pH 7, the MRPs solutions exhibited high antibacterial activity with the reduction of ~ 4 log CFU/ml over control sample. Furthermore, 5-hydroxymethylfurfural (5-HMF), a known cytotoxic product formed by heat-induced Maillard reaction was not detected in both irradiated CTS-GA and OC-GA solution. These results proved that the irradiation-induced Maillard reaction is an effective strategy to modify chitosan, and the MPRs of CT/OS with GA had a great potential to use as a natural preservative for food applications.